2019
DOI: 10.1109/jtehm.2019.2923628
|View full text |Cite
|
Sign up to set email alerts
|

Feature Extraction Based Machine Learning for Human Burn Diagnosis From Burn Images

Abstract: Burn is one of the serious public health problems. Usually, burn diagnoses are based on expert medical and clinical experience and it is necessary to have a medical or clinical expert to conduct an examination in restorative clinics or at emergency rooms in hospitals. But sometimes a patient may have a burn where there is no specialized facility available, and in such a case a computerized automatic burn assessment tool may aid diagnosis. Burn area, depth, and location are the critical factors in determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(50 citation statements)
references
References 17 publications
0
50
0
Order By: Relevance
“…Studies in the literature used very deficient databases, the authors in [21] reported 73.2% accuracy on datasets of 164 images and all images were in L*a*b* colour space with the application of PCA for dimensionality reduction on texture features. Study in [22] reported overall accuracy of 82.43% using 74 images in L*a*b* colour space, another study in [23] reported a discriminatory accuracy of 79.4% using colour and texture features and DCNN as a classifier on a database of 450 images. In this proposed study, we used 1560 RGB burn images along with 520 healthy skin images thereby achieving stateof-the-art discriminatory accuracy of 95.43%.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in the literature used very deficient databases, the authors in [21] reported 73.2% accuracy on datasets of 164 images and all images were in L*a*b* colour space with the application of PCA for dimensionality reduction on texture features. Study in [22] reported overall accuracy of 82.43% using 74 images in L*a*b* colour space, another study in [23] reported a discriminatory accuracy of 79.4% using colour and texture features and DCNN as a classifier on a database of 450 images. In this proposed study, we used 1560 RGB burn images along with 520 healthy skin images thereby achieving stateof-the-art discriminatory accuracy of 95.43%.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Discriminating burns depth using machine learning was also reported in a study by [22]. The aim is to provide a reliable diagnostic technique to deduce whether a sustained burn injury requires surgical intervention or not because early determination of right treatment choice can shorten the healing time.…”
Section: Literaturementioning
confidence: 94%
“…Convolutional neural networks (CNNs) have been used in the past for burn classification. In one study, CNNs were used to produce feature maps that were fed to a support vector machine (SVM) for classification and an accuracy of 82.43% was achieved [8]. Others have also experimented with CNN architectures for burn degree determination.…”
Section: Previous Deep Learning Researchmentioning
confidence: 99%
“…Another study by the authors in [22] used 74 burn images in LAB colour space from Caucasian patients to discriminate burns using machine learning. The approach used handcrafted features to train a SVM which achieved a classification accuracy of 82.43%.…”
Section: Literature Reviewmentioning
confidence: 99%